Pelatihan Pengolahan Makanan dengan Bahan Hasil Pertanian Masyarakat - Wijayanti, Ani; Hari Putri, Emmita Devi; Mayasari, Citra Unik; Nurul Hakim, M Fathurrahman; Fiyan, Miftah Arif; Nugroho, Dhimas Setyo (Sekolah Tinggi Pariwisata AMPTA, 2020)
The Sosok Peak tourist destination in the village of Bawuran has abundant natural resources in the form of Moringa plants. Until now, the community has not been able to use Moringa plant to be used as a variety of processed products and has a resale value. This community service program aims to increase the knowledge and skills regarding the use of Moringa leaves. To train and grow an entrepreneurial spirit to the community so that it can improve the economy of the Bawuran village community. The targets of community service activity are the people of Bawuran village, Sosok Peak’s tourism manager and the merchants. The method used in this community service is carried out in several stages including identification, socialization, training and assistance. Community service has provided several benefits to the community, namely an increase in community knowledge about the benefits of Moringa and its use as well as introducing an entrepreneurial spirit. For traders, they can increase their knowledge about processing various food products that can be sold at Sosok Peak. For the tourism manager, this training can create a product image (typical food) for the Sosok Peak tourist destination.